The most frequent cause agents of the urinary tract infection among children and their sensitivity to treatment with antibiotics - Jancic, Aleksandra Predrag; Vujic, Ana; Medovic, Rasa; Igrutinovic, Zoran (Medicinski časopis, 2012)
Abstract Introduction: Urinary infections are one of the most frequent in children's age and mostly caused by bacteria. Such as, they are significant source of morbidity in children and can indicate to some existing anomalies of urinary tract. Aims of the study: Finding out the causes of urinary infection among children in the last 5 years according to their sex and age and establishing their sensitivity to antibiotics. Sources and methods: Documents from the patient's history who were hospitalized on pediatric clinics from 1st January2005. to 31st December2009. were used. Urinoculture with antibiogram were the most important for this research. Using the χ2 test in the program SPSS11.0 the statistical data processing of the documents we collected, was done. Results: The number of children with diagnosis of urinary tract infection that was caused by Escherichia coli, Klebsiella, Proteus mirabilis and Enterococcus is 305, 63, 60 % of girls and 36, 39 % of boys. At girls the presence was like this : Escherichia coli 74,5%, Klebsiella 9,4%, Proteus mirabilis 4,7%, Enterococcus 2,8%  and in boys Escherichia coli 53,4%, Klebsiella18,3%, Proteus mirabilis 9,9%, Enterococcus 3,1%. The largest number of infected girls is in the age of infants, 29, 1% and boys in 55, 7%. Escherichia coli is equally sensitive to antibiotics we mentioned. Conclusion: Escherichia coli is the most frequent microbe that causes urinary infection. Comparing the age it's most frequently found at the age of infant and as to the sex it's more often with girls. Escherichia coli is equally sensitive to these antibiotics: Ceftiaxon, Amikacin, Cephalexin, Ofloxacin, Gentamicin, Pipemidinska kiselina. Key words: urinary infection, sensitivity, antibiotics